Percutaneous coronary intervention can be safely performed with left ventricular thrombus without increasing stroke risk: A 5-year retrospective review using real-world data - Mohanad Shehadeh (17860691) (2023)
Introduction Left ventricular thrombus (LVT) increases the risk of ischemic stroke. However, it remains uncertain if the percutaneous coronary intervention (PCI) in the confirmed LVT setting further augments the stroke risk. Therefore, in this study, we evaluated the risk of stroke among patients with LVT undergoing CAG +/− PCI. Methods This retrospective observational cohort study included all the patients encountered with LVT from 1st of April 2015, to 31st of March 2020. The study population was divided into two groups: Longobardo et al. (2018) [[1]] patients with LVT who underwent CAG +/− PCI; Solheim et al. (2010) [[2]] patients with LVT who did not undergo CAG +/− PCI. The primary outcome evaluated was stroke during the index admission, and the secondary outcomes included in-hospital mortality, all-cause mortality, and stroke at 12 months post-discharge. Logistic regression was used to determine the risk of stroke associated with PCI among patients with LVT, and a p-value<0.05 indicated statistical significance. Results Of the 210 patients included, 119 underwent CAG +/− PCI, while 91 patients did not undergo CAG +/− PCI. Most of the patients were Asian (67%), male (96%), with a mean age of 56 years. Ischemic cardiomyopathy was the primary etiology of LVT in both groups (96% in the CAG +/− PCI group and 80% in non CAG +/− PCI group). During the index admission, stroke among patients with LVT did not differ between the CAG +/− PCI and non CAG +/− PCI groups (5% versus 3.3%; odds ratio (OR) 1.6, 95% confidence interval (CI) 0.34–6.4, p = 0.539; adjusted OR 0.9, 95% CI 0.09–10.6, p = 0.968). Similarly, in-hospital mortality, all-cause mortality, and stroke at 12 months did not differ between the study groups. Conclusion Performing CAG +/− PCI among patients with LVT was not associated with an increased risk of stroke during admission or within 12 months in comparison to patients who did not undergo CAG +/− PCI, which may reassure cardiologists to perform CAG +/− PCI among patients with LVT safely. Other Information Published in: International Journal of Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijcard.2023.131415